Efeitos da lectina de Canavalia maritima (ConM) na biodisponibilidade do fitohormônio ácido indol-3-acético (AIA) em segmentos foliares de Nicotiana tabacum cultivados in vitro - Sales, Misrael Vieira (2024)
Lectins are proteins widely distributed in plants and are particularly abundant in the cotyledons of some species. In legumes, these proteins have a highly conserved hydrophobic region, which can enhance their interactions with hydrophobic molecules, such as plant hormones. The present study aimed to evaluate the physiological function of ConM, a lectin isolated from the seeds of Canavalia maritima, in interaction with the auxin indole-3-acetic acid (IAA), using leaf segments of Nicotiana tabacum cultured in vitro. The leaf segments were vacuum-infiltrated with a solution containing 20 µM of IAA and different concentrations of ConM (5 µM, 20 µM, and 40 µM), and then cultured in MS medium without growth regulators for 28 days at 26°C, with a 12-hour photoperiod. Biomass accumulation, photosynthetic pigments, antioxidant enzyme activity, and lipid peroxidation were analyzed. The expression of auxin-regulated genes (ARF1, IAA14, IAA17, and SAUR59) was quantified by qRT-PCR. Data were statistically analyzed using Tukey's test at 5% probability, via Prism® software. It was found that the concentration of 40 µM of ConM reduced chlorophyll a content by 33.52% and increased chlorophyll b content by 24.29% compared to the control. Concentrations of ConM below 40 µM promoted callus induction, while 40 µM of ConM significantly reduced callus formation and fresh and dry biomass. Furthermore, ConM concentrations of 20 µM and 40 µM increased lipid peroxidation in leaf segments by 25% and 50%, respectively. In calli formed under 5 µM of ConM treatment, a 39.59% increase in soluble proteins was observed, while 40 µM resulted in a 25.53% reduction. In leaf segments treated with 20 µM of ConM, significant increases in the activity of APX (16.77%), CAT (82.76%), and POX (56.34%) enzymes were observed. Different concentrations of ConM significantly altered the expression patterns of the studied genes. At 0h, ConM concentrations of 5 µM and 20 µM increased the expression of ARF1 and IAA14, while the 40 µM concentration repressed ARF1 expression. In the first 48 hours, IAA14 expression increased; however, at the 40 µM concentration, a significant reduction in this gene’s expression was observed, indicating negative modulation. The interaction of ConM with IAA reduced auxin bioavailability, triggering a molecular response through the expression of auxin-regulated genes, leading to significant morphological, biochemical, and physiological changes.